Young adults on the perceived benefits and expected use of personal health records: a qualitative descriptive study. Issue 1 (1st January 2016) - Nguyen, Quynh; Bartlett, Gillian; Tellier, Pierre-Paul; Rodríguez, Charo
Abstract : Background: Personal health records (PHRs) are tools that allow individuals to access, share and manage their health information online. Despite apparent interest, adoption rates remain low. There is a gap in our understanding as to what different populations of users, in particular young adults, might want from such a tool. Objective: To describe and interpret the views and expectations of young healthy adults about using an online PHR. Methods: A qualitative descriptive study was carried out. Four focus groups were conducted with a total of 29 participants (18–34 years old) from a community setting in Montreal, Canada. Interviews were transcribed and analyzed with inductive thematic analysis. Results: With respect to how young adults viewed PHRs, three broad themes were identified: perceived advantages to using a PHR, future PHR users and concerns about PHRs. Three other overarching themes emerged from data analysis in terms of what participants expected from using a PHR: the use of the PHR for preventative health, PHR support to take more control over their health and strategies to make the PHR worthwhile. A conceptual framework of factors influencing expectations of PHR use in this population is proposed. Conclusions: While young adults view the PHR as beneficial, this is not enough for them to be motivated to actually use a PHR. To foster use, the PHRs need to be perceived as a health prevention tool that helps users to increase control over their health status. More research is needed to understand the expectations and anticipated use of different populations in designing a person-centered tool;the proposed framework provides theoretical basis in this regard.